IMPLEMENTASI KODE ETIK GURU DALAM PROSES PEMBELAJARAN DI MAN 1 SOPPENG - Rusmin B, Muhammad; Abidin, Nurul Aynun; Mosiba, Risna (Inspiratif Pendidikan, 2022)
This study discusses the implementation of the teacher’s code of ethics in the learning process at MAN 1 Soppeng. The conclusion of this research is that the implementation of the teacher’s code of ethics in the learning process at MAN 1 Soppeng has been able to be applied by educators at the school. Factors that support the implementation of the teacher’s code of ethics in the learning process at MAN 1 Soppeng are the personal factors of the educators themselves, educational facilities and infrastructure and support from students. The inhibiting factor in implementing the teacher’s code of ethics in the learning process at MAN 1 Soppeng is that the description of the teacher’s code of ethics is not yet clearly understood by educators and students are also difficult to deal with because they have a variety of different characters. The solution is that educators must strive to develop and improve the quality of their profession and the government must pay attention to the welfare of educators and appreciate every effort made by educators to educate the nation’s life. However, overall the researchers view that educators at MAN 1 Soppeng have been able to implement the code of ethics.